Pengaruh ekonomi pembangunan terhadap sumber daya manusia di Indonesia - Machfud, Muhammad Muhajir (Maliki Interdisciplinary Journal, 2024)
High economic growth in Indonesia over the last few decades has made a major contribution to improving human resources in this country. increasing per capita income and access to better education have helped improve the quality of human resources in Indonesia. Education is a key factor in human resource development in Indonesia. The government’s efforts to improve access and quality of education, as well as increasing the portion of the education budget from the APBN, have helped improve the quality of human resources in Indonesia. This can be seen from increasing literacy rates and school participation, as well as improving the quality of education and increasing skill abilities